Nanotechnological approaches for treating skin cancer : from drug delivery nanoformulations to 3D models of skin cancer - Rosadas, Marta Oliveira Vasconcelos (2022)
Basal cell carcinoma is the most common skin cancer in the world. Even though its mortality rates are low, the number of cases has been rising worldwide. Photodynamic therapy mediated by 5-aminolevulinic acid (5-ALA) is a possible treatment for this kind of cancer. However, the penetration capability of 5-ALA into the deeper layers of the skin is limited, constraining the potential of this therapy. To overcome this limitation, phosphocholine-based nanovesicles were developed, using a pH gradient active loading protocol, to serve as a drug delivery system and to improve the transdermal passage of 5-ALA. The vesicles were characterized by morphology, encapsulation efficiency, loading capacity, stability, and diffusion capacity using ex-vivo pig skin. Additionally, a 3D cellular model was developed to resemble skin cancer, using a collagen hydrogel as a scaffold. Cellular tests were conducted using this skin model, which evaluated the vesicles' toxicity and penetration capability. Furthermore, preliminary tests of the efficacy of this therapy were carried out with 2D melanoma cells. According to the results, with a feeding concentration of 833 μg/mL of 5-ALA, its encapsulation efficiency is 24%. The vesicles presented an average diameter of 154,8 ± 18,8 nm, which decreased slightly until day 15 of storage, from when the sample stabilized. The vesicles have good thermostability. The diffusion tests showed that the vesicles could penetrate the skin, therefore, have the potential as a transdermal drug delivery system. Though the tumor target of this project is basal cell carcinoma, cellular tests have been performed with melanoma cells. The results show the therapeutic potential of the vesicles upon application of the photodynamic stimulus. In addition, preliminary studies with 3D hydrogel models of skin cancer embedded with melanoma spheroids and overlayed with keratinocytes demonstrate the capability of the vesicles to penetrate the matrix and enter the spheroids.